Non-verbal communication in the poetry of Sergei Yesenin and the methods of translating it into Polish - Curkan-Dróżka, Ełona (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2018)
The article presents the results of a study on the role of non-verbal communication (gestures and facial expressions) in the poetry of Sergei Yesenin, as well as on the methods of translating thereof into Polish. The author of the article emphasises the communicative potential of these means and the diversity of information transmitted that way. Particular attention is paid to how the features of Yesenin’s individual writing style (such as anthropomorphisation of nature) are expressed with the use of non-verbal communication. The paper brings an analysis of selected translation techniques, as well as of the impact on the poetic text of the transformations applied in the translation process.